MEDIA EDUKASI PROMOSI KESEHATAN MELALUI FILM DALAM MENUMBUHKAN PENGETAHUAN, SIKAP DAN PERILAKU KESEHATAN REPRODUKSI PADA REMAJA - Besar Tirto Husodo; Novia Handayani; Ulfa Velia Aisyiyah Purnamawati (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2021)
One way to provide adolescent reproductive health education is through film media. Films are a collection of events that occur in unique human life and are poured into the screen. Signs produced by humans are used as visuals that can be seen from various perspectives and provide a separate message for each individual. “Dua Garis Biru” is a form of reproductive and sexual health promotion in form of movie for teenager, which is an attractive ways for teenager to understand the information about reproductive and sexual health. This study aims to explain how the understanding of reproductive health content delivered through the movie